The age of micropop : The new generation of Japanese artists - Fogle, Douglas; Matsui, Midori; Mori, Tsukasa (Mito : Contemporary Art Center Art Tower Mito Mito-shi, 2007)
Aoki, Ryoko ; Arima, Kaoru ; Handa, Masanori ; Izumi, Taro ; K.K. ; Kunikata, Mahomi ; Mori, Chihiro ; Nara, Yoshitomo ; Noguchi, Rika ; Ochiai, Tam ; Oki, Hiroyuki ; Shimabuku ; Sugito, Hiroshi ; Takano, Aya ; Tanaka, Koki
Engels & Japans
The door into summer : The age of micropop, Contemporary Art Center Art Tower Mito, Mito-shi, 2007-02-03. 2007-05-06
boek
Keywords: Japan